(untitled) (Journal of Health Sciences, 2018)
Cardiovascular diseases (CVDs) are the major cause of disability and premature death all over the world. Annually, 17.5 million people die from CVDs, representing 30% of the total number of deaths. Despite established guidelines for the treatment of acute coronary syndrome, cardiac weakness, atrial fibrillation and CVD prevention, many patients remain inadequately treated, particularly in less developed nations. A brief overview of the development of CVDs, description of the current practice guidelines, and a cross sectional analyses of the status of CVD prevention and control in the Federation of Bosnia and Herzegovina is given. In the past 7 years, there has been a steady increase in deaths, where half of all deaths in the Federation of Bosnia and Herzegovina are attributed to CVDs. Deaths from the acute myocardial infarction had a rate of 91.0/100,000 inhabitants, a significant increase compared to 2010, when this rate was 69.2. The second leading cause of death, a stroke, with a rate of 87.1 showed a slight decrease compared to 2010, when it was 89.9. The third leading cause of death, heart failure, with a rate of 68.4, has a slight decrease compared to 2010, when the rate was 75.7. CVDs are the leading cause of mortality in Federation of Bosnia and Herzegovina, which, in addition to the large number of premature deaths, also causes major costs for the health sector and economy.